976765
contestada

Which shows the correct substitution of the values a, b, and c from the equation –2 = –x + x2 – 4 into the quadratic formula?

Quadratic formula: x =



Respuesta :

W0lf93
A quadratic equation is an equation of the form ax^2 + bx + c =0. Given the equation: -2 = -x + x^2 - 4, we write it in the form of a standard quadratic equation as follows: x^2 - x - 4 + 2 = 0 x^2 - x - 2 = 0 Comparing this with the standard quadratic equation gives that a = 1, b = -1 and c = -2 Therefore, the correct substitution of the values of a, b and c from the given equation into the quadratic formular is: x = [-(-1) + or - sqrt((-1)^2 - 4 x 1 x -2)] / (2 x 1)

Answer:

D on edng

Step-by-step explanation:

CAUSE I TOOK THE TEST